Przekształć iloczyny na sumy ( wykonaj mnożenia) i tam, gdzie to jest możliwe, wykonaj redukcjię wyrazów podobnych:

a) (2x+3y)(2x-3y)=

b) (4a-2b)(3a+b)=

c) (xy-x)(3xy+3x)=

d) (-3x²+y)(2x²+2x)=

e) (a-b)(a²-2a+2)=

f) (2x+5y)(x-3y+1)=

g) (3x-3y)(x+y-3)=

h) (2x-6y)(5x+2y)=

2

Odpowiedzi

2009-10-13T19:00:20+02:00
A) (2x+3y)(2x-3y)=4x²-6y+6xy-9y=4x²-15y+6xy
b) (4a-2b)(3a+b)=12a²+4ab-6ab-2b²=12a²-2ab-2b²
c) (xy-x)(3xy+3x)=3x²y²+3x²y-3x²y-3x²= 3x²y²-3x²

d) (-3x²+y)(2x²+2x)=-6x(do 4 potęgi)-6x³+2x²y+2xy

e) (a-b)(a²-2a+2)=a³-2a²+2a-ba²+2ab-2b

f) (2x+5y)(x-3y+1)=2x²-6xy+2x+5xy-15y²+5y=2x²-xy+2x-15y²+5y

g) (3x-3y)(x+y-3)=3x²+3xy-9x-3xy-3y²+9y=3x²-9x+9y

h) (2x-6y)(5x+2y)=10x²+4xy-30xy-4y²=10x²-26xy-4y²
4 3 4
Najlepsza Odpowiedź!
2009-10-13T19:00:59+02:00
A)(2x+3y)(2x-3y)= 4x²- 6 xy + 6 xy - 9 y²= 4x²-9y²

b)(4a-2b)(3a+b)=12a + 4ab - 2ab -2b²= 12a + 2ab - 2b²

c)(xy-x)(3xy+3x)= 3xy²+ 3x²y- 3x²y- 3x²= 3xy²- 3x²

d) (-3x²+y)(2x²+2x)=- 6x⁴- 6x³+ 2x²y +2xy

e) (a-b)(a²-2a+2)=a³-2a²+2a-ba²+2ab-2b

f) (2x+5y)(x-3y+1)=2x²-6xy+2x+5xy-15y²+5y=2x²-xy+2x-15y²+5y

g) (3x-3y)(x+y-3)=3x²+3xy-9x-3xy-3y²+9y=3x²-9x+9y

h) (2x-6y)(5x+2y)=10x²+4xy-30xy-4y²=10x²-26xy-4y²
4 3 4